Surface modification of Sr2Fe1.5Mo0.5O6-δ perovskite electrode with Ru nanoparticles via plasma-enhanced atomic layer deposition for solid oxide fuel cells - Shin, Jeong Woo (2025)
This study demonstrates the use of plasma-enhanced atomic layer deposition (PEALD) to deposit uniformly distributed Ru nanoparticles on a Sr2Fe1.5Mo0.5O6-δ (SFMO) perovskite cathode as a surface modification strategy to improve electrode performance. The PEALD Ru nanoparticles covered the SFMO surface with superior uniformity and high density, significantly enhancing the surface reaction steps of oxygen reduction reactions (ORR). SOFCs with Ru-coated SFMO cathode showed a peak power density of 983 mW/cm2 at 700 °C, a 47 % increase over the SOFCs using bare SFMO cathode. In addition, the presence of high-density Ru nanoparticles also suppressed the Sr surface segregation, which is a chronic issue that deteriorates the long-term stability of Sr-containing perovskite electrodes. The cell performance was maintained for more than 20 h without significant degradation compared to cells using a bare SFMO cathode.